Daytime plasma cortisol and cortisol response to dexamethasone suppression are associated with a prothrombotic state in hypertension - Brosolo, Gabriele; Da Porto, Andrea; Bulfone, Luca; Vacca, Antonio; Bertin, Nicole; Vivarelli, Cinzia; Catena, Cristiana; Sechi, Leonardo A. (Frontiers in Endocrinology, 2024)
A prothrombotic state was demonstrated in patients with Cushing's syndrome and is involved in the development and progression of cardiovascular and renal damage in hypertensive patients. This study was designed to examine the relationships between cortisol secretion and the hemostatic and fibrinolytic systems in hypertension. Methods: In 149 middle-aged, nondiabetic, essential hypertensive patients free of cardiovascular and renal complications, we measured hemostatic markers that express the spontaneous activation of the coagulation and fibrinolytic systems and assessed daily cortisol levels (8 AM, 3 PM, 12 AM; area under the curve, AUC-cortisol) together with the cortisol response to dexamethasone overnight suppression (DST-cortisol). Results: Plasma levels of D-dimer (D-dim), prothrombin fragment 1+2 (F1+2), and von Willebrand factor (vWF) were progressively and significantly higher across tertiles of AUCcortisol and DST-cortisol, whereas no differences were observed in fibrinogen, tissue plasminogen activator, plasminogen activator inhibitor-1, antithrombin III, protein C, and protein S. D-dim, F1+2, and vWF were significantly and directly correlated with age and both AUCcortisol and DST-cortisol. Multivariate regression analysis showed that both AUC-cortisol and DST-cortisol were related to plasma D-dim, F1+2, and vWF independently of age, body mass index, blood pressure, and renal function.Greater daily cortisol profile and cortisol response to overnight suppression are independently associated with a prothrombotic state in hypertensive patients and might contribute to the development of organ damage and higher risk of cardiovascular complications.